Trends and findings of lipoprotein(a) testing and associated cardiovascular disease profiles: a large single-center study from the Middle East-Gulf region - Manla, Yosef; AbdelWareth, Laila; Shantouf, Ronney; Aljabery, Yazan; St John, Terrence Lee; Sabbour, Hani; Piechowski-Jozwiak, Bartlomiej; Almahmeed, Wael (Frontiers in Cardiovascular Medicine, 2024)
Background Lipoprotein(a) [Lp(a)] is a genetically determined risk factor for atherosclerotic cardiovascular disease (CVD). Limited data are available on Lp(a) testing from the Middle-East region. Therefore, we aim to evaluate the utilization and yield of Lp(a) testing over time and characterize CVD profiles of patients with abnormal Lp(a) tasting at a single-quaternary-care center in the United Arab Emirates. Methods Unique Lp(a) tests conducted between 07/2017 and 10-2023 were included. Overtime trends in Lp(a) test utilization and abnormal Lp(a) [defined as Lp(a) > 125 nmol/L] test findings were described. CVD rates in patients with abnormal Lp(a) were compared to those with Lp(a) ≤ 125 nmol/L using appropriate methods. Results In our center, 0.95% of the patients (n = 5,677) had their Lp(a) measured, with a median level of 32 [11–82] nmol/L. Lp(a) was abnormal in 15.9% of the tests. Over the years 2018–2022, there was a 109% increase in Lp(a) testing, with concomitant up-trends in findings of abnormal Lp(a) (11.8% to 16.4%, P = 0.02). Compared to patients with Lp(a) ≤ 125 nmol/I, those with abnormal Lp(a) had higher rates of any prevalent CVD (34% vs. 25.1%, P < 0.001), CAD (25.6% vs. 17.7%, P < 0.001), HF (6.5% vs. 3.8%, P < 0.001), and stroke (7.1% vs. 4.4%, P < 0.001). Conclusion Almost one in six patients tested for Lp(a) had abnormally elevated Lp(a), and CVD was prevalent in one-third of the patients who tested abnormal for Lp(a). The study highlights the growing awareness of the relevance of Lp(a) for CVD risk stratification and prevention.